Analysis of the Evolution of Tannic Acid Stabilized Gold Nanoparticles Using Mie Theory - Assia Rachida Senoudi; Sidi Mohammed Chabane Sari; Ilhem Faiza Hakem (International Journal of Analytical Chemistry)
Spherical gold nanoparticles (GNPs) have been synthesized in aqueous solutions using sodium citrate (SC) and tannic acid (TA) as reducing and stabilizing agents. Upon addition of TA and compared to the GNP TA-free aqueous solutions, a reduction of the GNPs size and consequently a dramatic change of their optical properties have been observed and quantitatively analyzed using Mie theory. An increase in the concentration of TA reveals a modification of the colloidal solution refractive index that is evidenced by the shift in the peak position of the localized surface plasmon resonance (LSPR) band. The variations of the peak absorbance with the TA concentration are examined in the low and high concentration regimes.